2022
DOI: 10.3389/fimmu.2022.896874
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Interferes With Quorum-Sensing in Pseudomonas aeruginosa and Modulates Inflammatory Responses In Vitro and In Vivo

Abstract: Developing quorum-sensing (QS) based anti-infection drugs is one of the most powerful strategies to combat multidrug-resistant bacteria. Paeonol has been proven to attenuate the QS-controlled virulence factors of P. aeruginosa by down-regulating the transcription of QS signal molecules. This research aimed to assess the anti-virulence activity and mechanism of paeonol against P. aeruginosa infection in vitro and in vivo. In this study, paeonol was found to reduce the adhesion and invasion of P.aeruginosa to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The present study showed that the level of serum LPS was increased and positively correlated with the abundance of Pseudomonas aeruginosa in GAD patients. Previous studies also reported that Pseudomonas aeruginosa induces macrophages to release various proinflammatory cytokines and chemokines through activation of the TLR4/MyD88/NF-κB signaling pathway ( 49 , 50 ). Our results provide evidence for the association between systemic inflammatory response and ear canal dysbiosis.…”
Section: Discussionmentioning
confidence: 89%
“…The present study showed that the level of serum LPS was increased and positively correlated with the abundance of Pseudomonas aeruginosa in GAD patients. Previous studies also reported that Pseudomonas aeruginosa induces macrophages to release various proinflammatory cytokines and chemokines through activation of the TLR4/MyD88/NF-κB signaling pathway ( 49 , 50 ). Our results provide evidence for the association between systemic inflammatory response and ear canal dysbiosis.…”
Section: Discussionmentioning
confidence: 89%
“…It has been demonstrated to exert a wide range of activities, spanning from immune regulatory activity [88], anti-inflammatory [89], to antibacterial effect [90,91]. Paeonol efficiently reduces infection of macrophages by P. aeruginosa, as described recently [92]. Furthermore, it has the potential to drastically impede the expression of QS-regulated gene rhlI/R and pqsA/R [93].…”
Section: Natural Molecules Reducing Pseudomonas Aeruginosa Growthmentioning
confidence: 89%
“…1 Paeonol effects on Pseudomonas aeruginosa infected macrophages. Based on the work of Tang H et al (2022) [ 92 ]. Pathogen bacteria and their genes are in yellow, macrophage is in blue and the components of immune system in other colours …”
Section: Main Textmentioning
confidence: 99%
“…Quantitative gene expression analysis was carried out on CFX Connect™ Real-Time PCR Detection System (Bio-Rad Laboratories, Segrate, Italy), using SYBR ® Select Master Mix for CFX (Life Technologies, Carlsbad, CA, USA) and ubiquitin for normalization. The primers used for real-time PCR analysis are reported in Table 2 [ 78 , 80 , 99 , 100 ].…”
Section: Methodsmentioning
confidence: 99%